Perancangan Sistem Informasi Akuntansi Penjualan pada A&W Restaurant Cabang Bip Bandung - Muharamani, Adelia; Regawan, Gugun; Kurniawati, Rina (STIKOM Tunas Bangsa Pematangsiantar, 2023)
This research designs and makes a sales accounting information system application program at A&W restaurant. The rapid development of technology affects many aspects, one of which is the economic aspect. Competition between business actors is getting tougher. In order to compete in the market, efforts are needed to improve the quality of work, service quality and data accuracy. Management of Sales Accounting Information Systems at fast food restaurant companies is still not optimal, namely still using manual recording and recapitulation on POS (point of sales) machines so that errors often occur due to inaccuracy between POS (point of sales) machines with sales recaps and the time used also inefficient. The research was conducted with data collection techniques using data triangulation based on observations, interviews and documentation. The results of this study will be designed a web-based sales accounting information system using mysql data processing and implemented into the php programming language with the aim of providing the needs for managing sales information at fast food restaurant companies and producing the required reporting more effectively and efficiently.